1999
DOI: 10.1002/(sici)1521-3773(19990802)38:15<2188::aid-anie2188>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Structure of Precipitated Nanosize β ‐Carotene Particles

Abstract: A combination of analytical methods and molecular modeling calculations has provided a detailed picture of the supramolecular and microscopic structure of precipitated lipophilic carotenoids. The nanoparticles have a core/shell structure (see schematic representation) in which the particle core (120 nm) consists of a variety of molecular aggregates of different sizes, and the shell (40 nm) consists of an adsorbed gelatin layer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
139
0
5

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 233 publications
(156 citation statements)
references
References 5 publications
11
139
0
5
Order By: Relevance
“…However, the purchased b-carotene powder showed several sharp XRD peaks and was highly crystalline. Auweter et al 62 reported that b-carotene particles in the 100-200 nm size range exhibited some crystallinity. They produced their particles by precipitation from an alcohol solution with water and gelatin as a stabilizer.…”
Section: Crystallinity Of Nanoparticlesmentioning
confidence: 99%
“…However, the purchased b-carotene powder showed several sharp XRD peaks and was highly crystalline. Auweter et al 62 reported that b-carotene particles in the 100-200 nm size range exhibited some crystallinity. They produced their particles by precipitation from an alcohol solution with water and gelatin as a stabilizer.…”
Section: Crystallinity Of Nanoparticlesmentioning
confidence: 99%
“…Taking DHP-1 as an example, it was found that its absorption spectra exhibited no significant change until the water volume fraction (f w ) was increased to 70% where the entire absorption spectra showed dramatic decrease (Fig. 2a), meanwhile, there was an obvious leveled-off tail in the visible region due to light-scattering effect because of the formation of nanoscopic aggregates [40]. The pure THF solution of DHP-1 emitted weak green light, which was ascribed to the free rotation of the phenyl ring and DHP ring around the CeC bond facilitating a non-radiative relaxation process [1,23].…”
Section: Aie Properties Of Dhp Derivativesmentioning
confidence: 99%
“…30 Some researchers have developed water-dispersible formulations as carriers to entrap carotenoids and direct them to in vitro and in vivo systems. [31][32][33][34] The polymer-based delivery system consisting of nanoscale carriers provides an alternative mode of carotenoid delivery. These formulations have shown increased physiochemical stability of the encapsulated β-carotene.…”
Section: Introductionmentioning
confidence: 99%